The dynamic geophysical environment of (101955) Bennu based on OSIRIS-REx measurements - Scheeres, DJ; McMahon, JW; French, AS; Brack, DN; Chesley, SR; Farnocchia, D; Takahashi, Y; Leonard, JM; Geeraert, J; Page, B; Antreasian, P; Getzandanner, K; et al. (Springer Nature, 2019)
The top-shaped morphology characteristic of asteroid (101955) Bennu, often found among fast-spinning asteroids and binary asteroid primaries, may have contributed substantially to binary asteroid formation. Yet a detailed geophysical analysis of this morphology for a fast-spinning asteroid has not been possible prior to the Origins, Spectral Interpretation, Resource Identification, and Security-Regolith Explorer (OSIRIS-REx) mission. Combining the measured Bennu mass and shape obtained during the Preliminary Survey phase of the OSIRIS-REx mission, we find a notable transition in Bennu’s surface slopes within its rotational Roche lobe, defined as the region where material is energetically trapped to the surface. As the intersection of the rotational Roche lobe with Bennu’s surface has been most recently migrating towards its equator (given Bennu’s increasing spin rate), we infer that Bennu’s surface slopes have been changing across its surface within the last million years. We also find evidence for substantial density heterogeneity within this body, suggesting that its interior is a mixture of voids and boulders. The presence of such heterogeneity and Bennu’s top shape are consistent with spin-induced failure at some point in its past, although the manner of its failure cannot yet be determined. Future measurements by the OSIRIS-REx spacecraft will provide insight into and may resolve questions regarding the formation and evolution of Bennu’s top-shape morphology and its link to the formation of binary asteroids.